Phytochemicals Modify the Action of Cancer Cells Mitochondrial Drug-Resistance Mechanism (Sciences of Pharmacy, 2023)
The genesis and evolution of cancer are known to be significantly influenced by mitochondria, and recent studies have indicated that mitochondrial modifications may potentially contribute to the emergence of treatment resistance. Additionally, drug-resistant cancer cells may also display modifications in mitochondrial metabolism, such as changes in the generation of reactive oxygen species (ROS), which are biological byproducts of mitochondrial respiration. These changes can alter the cell's sensitivity to chemotherapy drugs and contribute to drug resistance. The expression of specific genes or proteins that are crucial in the control of cell growth and survival may be altered by mitochondrial mutations, which may also contribute to medication resistance. Phytochemicals are naturally occurring, biologically active substances found in plants that have been demonstrated to offer a variety of health advantages, including anti-cancer effects. It has been demonstrated that phytochemicals target these altered mitochondrial pathways in cancer cells, increasing the potency of chemotherapy medications and overcoming drug resistance. For instance, it has been demonstrated that some phytochemicals, including curcumin, resveratrol, and quercetin, can block the function of mitochondrial membrane proteins that lead to drug resistance in cancer cells. Other phytochemicals, including berberine and epigallocatechin gallate (EGCG), have been demonstrated to directly interfere with mitochondrial activity, inducing apoptosis (programmed cell death) in cancer cells. Overall, the capacity of phytochemicals to modify the functioning of cancer cell mitochondrial drug-resistance systems is a viable strategy for the creation of novel anti-cancer treatments.